Hydrophobic modified asphalt mixture and preparation method thereof
By using hydrophobic modifiers prepared from silane compounds to compositely modify asphalt and aggregates, the problem of poor water damage resistance in the existing technology is solved, higher water stability and adhesion are achieved, and extended Extend the service life of the road surface and improve driving safety.
Patent Information
- Application Number
- CN202411483897.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
The existing hydrophobic modified asphalt mixtures are only single modifications for aggregates, and the composite modification of asphalt and aggregates is not achieved, resulting in poor water damage resistance.
The use siliconate, metharxyl oxide, and acrylics such as acrylics, etc. are used to prepare hydrophobic modifiers such as Silicane and other silicanes. Asphalt mixture.
Through the compounding of asphalt and material collection, the water resistance damage performance of the asphalt mixture is significantly improved, and its water stability and adhesion in the humid and rainy environment are enhanced, which extends the service life of the pavement and improves the service life of the pavement. Driving safety.
Smart Images

Figure CN119349930A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of road engineering materials, and in particular relates to a hydrophobic modified asphalt mixture and a preparation method thereof. Background Art
[0002] In recent years, with the continuous development of transportation infrastructure and the continuous improvement of highway construction standards, the durability, driving comfort and safety of the road surface have become important factors affecting road quality. Stone mastic asphalt (SMA) pavement has gradually been widely used in high-grade highways due to its good load-bearing capacity, anti-rutting performance, crack resistance and noise reduction effect. However, with the increase of service time, SMA pavement has exposed some typical diseases, among which water damage is particularly prominent.
[0003] Water damage refers to the decrease in the bonding force and structural strength of asphalt mixtures when they are eroded by water, which leads to pavement peeling, looseness, potholes and other defects, seriously affecting the service life of the pavement and driving safety. The rainy climate in the southern region makes the road surface in a humid environment for a long time, further exacerbating the problem of water damage. Due to the poor drainage performance of traditional SMA pavements, water often accumulates on the road surface. In severe cases, a water film will form, resulting in a decrease in friction between the tire and the road surface, increasing the risk of traffic accidents. Therefore, how to improve the water damage resistance of SMA pavements has become an important issue in highway construction.
[0004] Hydrophobic materials have a large number of hydrophobic groups on their surface, such as long-chain alkyl or fluorinated alkyl groups, which enable them to effectively repel water and show significant hydrophobic properties. In recent years, hydrophobic materials have gradually become an important choice for improving the water stability of asphalt mixtures due to their good chemical stability, durability and good performance in water environments. However, most of the existing hydrophobic modified asphalt mixtures only carry out single modification of aggregates, and fail to achieve composite modification of asphalt and aggregates, which makes the overall resistance to water damage still less than ideal. At the same time, existing research has mostly focused on testing under indoor water environment conditions, and has not fully considered the complex water environment of actual roads, such as seawater, acid rain, ordinary rainwater and other conditions.
[0005] Therefore, the development of a hydrophobic modified asphalt mixture that can simultaneously perform composite modification on asphalt and aggregate and exhibit excellent water stability under different water environment conditions has become the key to improving the water damage resistance of SMA pavements. This will not only help extend the service life of the pavement and improve driving safety, but will also significantly reduce the frequency and cost of highway maintenance and repairs. Summary of the invention
[0006] The purpose of the present invention is to provide a hydrophobic modified asphalt mixture and a preparation method thereof, so as to solve the problem that the existing hydrophobic modified asphalt mixture only performs single modification on aggregate, fails to achieve composite modification of asphalt and aggregate, and has poor water damage resistance.
[0007] The technical solution adopted by the present invention is:
[0008] The method for preparing a hydrophobic modified asphalt mixture comprises the following steps:
[0009] S1: preparing a hydrophobic modifier;
[0010] S2: Aggregate treatment with hydrophobic modifier;
[0011] S3: Treating asphalt with a hydrophobic modifier and preparing a hydrophobic modified asphalt mixture.
[0012] Further, the S1 includes:
[0013] S11: mix tetrabutyl orthosilicate and methyltriethoxysilane, add acrylate functionalized silane to the mixed solution, and then add anhydrous ethanol;
[0014] S12: heating and stirring the solution obtained in S11;
[0015] S13: adding deionized water to the solution obtained in S12 to perform a hydrolysis reaction, heating and stirring the solution; and simultaneously using ultrasound to assist the reaction;
[0016] S14: increasing the heating temperature to perform a condensation reaction, and performing a shearing treatment on the solution while stirring the solution;
[0017] S15: After the condensation reaction is completed, the solution is cooled and filtered to obtain a hydrophobic modifier.
[0018] Furthermore, in said S11,
[0019] The molar ratio of tetrabutyl orthosilicate to methyltriethoxysilane is (1:1) to (3:1);
[0020] The volume ratio of acrylate functionalized silane to tetrabutyl orthosilicate is 5% to 15%;
[0021] The volume ratio of anhydrous ethanol to the total volume of tetrabutyl orthosilicate and methyltriethoxysilane is 30%-50%.
[0022] Furthermore, in S12, the stirring speed is 500-600 rpm; the temperature is 50-60° C., and the stirring time is 20-40 minutes;
[0023] In S13, the volume of deionized water is 5-10% of the total volume of the solution obtained in S12, the temperature is 50-60° C., the stirring time is 10-20 minutes, the ultrasonic frequency is 25-35 kHz, and the ultrasonic action time is 10-20 minutes.
[0024] Furthermore, in S14, the temperature is 70-80° C., the stirring time is 30-40 minutes, the solution is sheared at a rotation speed of 2000-3000 rpm, and the shearing time is 20-30 minutes.
[0025] Further, the S2 includes:
[0026] S21: washing and drying the aggregate, and stirring in a stirrer;
[0027] S22: adding the prepared hydrophobic modifier into the stirrer of S21 and stirring;
[0028] S23: taking out the aggregate, cleaning it and heating it to obtain modified aggregate.
[0029] Furthermore, in S21, the aggregate is stirred in a stirrer for 5 to 7 hours;
[0030] In S22, the temperature is 20-30°C and the stirring time is 30-60 min;
[0031] In S23, after cleaning, the aggregate is placed in a heating container for heating at a temperature of 100 to 120°C.
[0032] Further, the S3 includes:
[0033] S31: heating the SBS modified asphalt to a flowable state;
[0034] S32: shearing the asphalt;
[0035] S33: adding the prepared hydrophobic modifier to asphalt;
[0036] S34: shearing the mixture obtained in S33 to obtain modified asphalt;
[0037] S35: heating the modified asphalt;
[0038] S36: Mixing the heated modified asphalt, modified aggregate, and filler to obtain a hydrophobic modified asphalt mixture.
[0039] Furthermore, in S31, the heating temperature is 155-165° C., and the heating time is 0.5-1 hour;
[0040] In S32, the asphalt is sheared at 160-175°C and the shearing speed is 1000-1500 r / min;
[0041] In S33, the mass of the hydrophobic modifier is 3% to 5% of the mass of the asphalt, and the hydrophobic modifier is added to the asphalt within 5 to 7 minutes;
[0042] In S34, the shearing speed is 3000-4000 r / min, and the shearing time is 30-50 minutes;
[0043] In S35, the heating temperature is 165 to 175°C and the heating time is 30 to 40 minutes.
[0044] Another technical solution adopted by the present invention is:
[0045] The hydrophobic modified asphalt mixture is prepared by the above method.
[0046] The beneficial effects of the present invention are
[0047] 1. Traditional hydrophobic modification methods are limited to aggregate modification, and most of them focus on a single hydrophobic modification treatment of aggregates, while ignoring the hydrophobic treatment of asphalt itself, resulting in insufficient composite modification effect of asphalt and aggregate, and unsatisfactory overall water resistance. The present invention uses three silane compounds with excellent performance, tetrabutyl orthosilicate (TBOS), methyltriethoxysilane (MTES) and acrylate functionalized silane (APMS), wherein the butoxy (-OC4H9) structure of TBOS makes its hydrolysis rate slow, and can provide a stable and continuous Si-O-Si cross-linked network generation process, and this slow hydrolysis helps to form a more compact coating structure. In contrast, the ethoxy (-OC2H5) hydrolysis rate of MTES is moderate, and under the synergistic effect with TBOS, it can show excellent thermal stability in a high temperature environment, and is not easy to volatilize or decompose, ensuring that the material maintains its structural integrity under harsh conditions, so the hydrophobic modifier can form a hydrophobic network structure on the surface of aggregates and asphalt, with better effectiveness and stability. The introduction of TBOS greatly enhances the high temperature resistance of the material, ensures the long-term stability of the coating at high temperatures, and extends the service life of the SMA asphalt pavement.
[0048] 2. The acrylate groups in APMS can participate in the cross-linking reaction, further improving the mechanical strength and chemical stability of the hydrophobic material.
[0049] 3. In the preparation process of the hydrophobic material of the present invention, a dense Si-O-Si structure is formed by the synergistic effect of TBOS and MTES, and the uniformity and performance stability of the hydrophobic material are ensured by ultrasonic-assisted hydrolysis, high-speed shearing treatment and other means.
[0050] 4. In a humid and rainy environment, moisture can easily penetrate into the interface between asphalt and aggregate, resulting in a significant decrease in the bonding force between asphalt and aggregate. This bonding failure can cause road surface diseases such as peeling, looseness and potholes, seriously affecting the service life of the road and driving safety. The hydrophobic modified asphalt mixture of the present invention has a stronger bonding force between asphalt and aggregate when exposed to high temperature or complex environment. The dense cross-linked network formed by the synergistic effect of the three materials significantly prevents the penetration of moisture, so it has better high temperature performance and stronger resistance to water damage. It can effectively prevent moisture from entering the asphalt-aggregate interface, enhance water stability, and avoid bonding failure caused by humid environment.
[0051] 5. Existing technologies mostly focus on testing water resistance in ordinary water environments, without fully considering the complex water environments that actual roads may face, such as seawater, acid rain, etc. The moisture in these environments will accelerate the degradation of pavement materials, making it difficult for traditional hydrophobic modification technology to meet the long-term water resistance requirements in practical applications. The hydrophobic modified asphalt mixture of the present invention performs better than the existing technology in rainy and humid environments and is suitable for a variety of road application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0053] Figure 1 It is a flow chart of the present invention.
[0054] Figure 2 It is a comparison chart of the rutting test results of Examples 1 to 7.
[0055] Figure 3 It is a comparison chart of the rutting test results of Comparative Examples 3 to 14.
[0056] Figure 4 It is a comparison chart of the low temperature bending beam test results of Examples 1 to 7.
[0057] Figure 5 It is a comparison chart of the low temperature bending beam test results of Examples 3 to 14.
[0058] Figure 6 It is a comparison chart of the results of the submerged Marshall test of Examples 1 to 7.
[0059] Figure 7 It is a comparison chart of the results of the immersion Marshall test of Comparative Examples 3 to 14.
[0060] Figure 8 It is a comparison chart of adhesion energy, stripping work and compatibility of asphalt mixtures prepared by SBS asphalt, Comparative Example 1, Comparative Example 2 and Example 1.
[0061] Fig. 9 It is a comparison chart of flow value and stability of asphalt mixtures prepared by SBS asphalt, Comparative Example 1, Comparative Example 2, and Example 1.
[0062] Fig.10 It is a comparison chart of freeze-thaw splitting test results of asphalt mixtures prepared by SBS asphalt, Comparative Example 1, Comparative Example 2, and Example 1. DETAILED DESCRIPTION
[0063] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] See also Figure 1 , the complete steps of this embodiment are as follows:
[0065] S1: Preparation of hydrophobic materials.
[0066] S11: Tetrabutyl orthosilicate (TBOS) and methyltriethoxysilane (MTES) are measured in a molar ratio of 1:3 to 4:1, mixed, APMS is taken according to the volume of acrylate functionalized silane (APMS): the volume of TBOS = 5% to 20%, added to the mixed solution, and then anhydrous ethanol is taken according to the volume of anhydrous ethanol: (total volume of TBOS and MTES) = 30%-50%.
[0067] S12: Place the three-necked flask on a constant temperature magnetic stirrer, stir at a speed of 500 rpm to 600 rpm, control the temperature at 50° C. to 60° C., and stir for 20 minutes to 40 minutes to fully dissolve and mix all the materials evenly.
[0068] S13: Deionized water is slowly added using a burette, the volume of the deionized water being 5-10% of the total volume of the solution, and stirring is continued at 50-60° C. for 10-20 minutes to start the hydrolysis reaction. At the same time, ultrasound is used to assist the hydrolysis reaction, the frequency is set to 25-35 kHz, and the ultrasound action time is 10-20 minutes.
[0069] S14: Raise the temperature to 60-90°C and continue stirring for 30-40 minutes to allow the silanol (Si-OH) generated by hydrolysis to undergo a condensation reaction to form a cross-linked network. During this process, use a high-speed shearing machine to shear the solution at a speed of 1500-4500 rpm for 15-45 minutes to ensure uniform condensation reaction and generate a dense hydrophobic modifier.
[0070] S15: After the condensation reaction is completed, the solution is naturally cooled to room temperature, and the insoluble matter is removed by filtration to obtain a uniform hydrophobic modifier solution.
[0071] S2: Treat the aggregate with a hydrophobic modifier. The hydrophobic modifier only needs to cover the surface of the aggregate.
[0072] S21: After the aggregate is thoroughly washed and dried with clean water, it is placed in a stirrer with small-sized grinding beads and stirred at room temperature for 5 to 7 hours to increase the surface roughness of the aggregate.
[0073] S22: Pour the hydrophobic modifier prepared in S15 into a stirrer, and stir at 20 to 30° C. for 30 to 60 minutes to allow the aggregate surface to fully contact with the hydrophobic modifier.
[0074] S23: Remove the aggregate and rinse it thoroughly with clean water, then put it into an oven at a temperature of 100-120°C to further promote the silicon-oxygen cross-linking reaction and ensure the stability and durability of the coating.
[0075] S3: Treating the asphalt with a hydrophobic modifier.
[0076] S31: Preheat the SBS modified asphalt in an oven at 155-165°C for 0.5-1 hour to heat it to a flowable state.
[0077] S32: The asphalt is then moved into a constant temperature heating sleeve, and the asphalt is sheared at a low speed of 1000 r / min to 1500 r / min at 160 to 175°C to eliminate bubbles in the asphalt.
[0078] S33: Using the external mixing method, within 5 to 7 minutes, take a hydrophobic modifier with a mass of 3% to 5% of the mass of the asphalt, slowly add it to the asphalt, and use a glass rod to assist in stirring.
[0079] S34: The mixture is sheared at a high speed of 3000 r / min to 4000 r / min for 30 to 50 minutes to ensure uniform dispersion of the modifier in the asphalt.
[0080] S35: Keep the modified asphalt in an oven at 165-175°C for 30-40 minutes to allow it to react fully.
[0081] S36: Preparation of hydrophobic modified asphalt mixture: According to the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTGE20-2011), the SMA asphalt mixture is designed for mix proportion and the optimal asphalt-stone ratio is determined. According to the determined optimal mix proportion and asphalt-stone ratio, the modified asphalt, modified aggregate and filler are mixed uniformly. The difference between the present invention and the ordinary SMA asphalt mixture is that the asphalt and aggregate are both hydrophobically modified.
[0082] Example 1
[0083] S1: Preparation of hydrophobic materials.
[0084] S11: Tetrabutyl orthosilicate (TBOS) and methyltriethoxysilane (MTES) were measured in a molar ratio of 2:1, and 10% of acrylate functionalized silane (APMS) and 40% of anhydrous ethanol were added.
[0085] Tetraethyl orthosilicate TEOS has a similar reaction mechanism to TBOS and can form a similar network structure, so TEOS can be used instead of TBOS here; methyltrimethoxysilane (MTMS) has a similar reaction mechanism to MTES, so MTMS can be used instead of MTES here.
[0086] S12: Place the three-necked flask on a constant temperature magnetic stirrer, stir at a speed of 550 rpm, control the temperature at 55° C., and stir for 30 minutes to ensure that all materials are fully dissolved and mixed evenly.
[0087] S13: Deionized water was slowly added using a burette, the volume of which was 8% of the total volume of the solution, and stirring was continued at 55° C. for 15 minutes to start the hydrolysis reaction. At the same time, ultrasound was used to assist the hydrolysis reaction, the frequency was set to 30 kHz, and the ultrasound action time was 15 minutes.
[0088] S14: The temperature was raised to 75°C and the stirring was continued for 35 minutes to allow the silanol (Si-OH) generated by hydrolysis to undergo a condensation reaction to form a cross-linked network. During this process, a high-speed shearing machine was used to shear the solution at a speed of 2500 rpm for 25 minutes to ensure uniform condensation reaction and generate a dense hydrophobic modifier.
[0089] S15: After the condensation reaction is completed, the solution is naturally cooled to room temperature, and the insoluble matter is removed by filtration to obtain a uniform hydrophobic modifier solution.
[0090] S2: Treat aggregate with a hydrophobic modifier.
[0091] S21: After the aggregate is thoroughly washed and dried with clean water, it is placed in a stirrer with small-sized grinding beads and stirred at room temperature for 6 hours to ensure the surface roughness of the aggregate.
[0092] S22: Pour the hydrophobic modifier prepared in S15 into a stirrer and stir at 25°C for 45 minutes to allow the aggregate surface to fully contact with the hydrophobic modifier.
[0093] S23: Remove the aggregate and rinse it thoroughly with clean water, then put it into an oven at a temperature of 110°C to further promote the silicon-oxygen cross-linking reaction and ensure the stability and durability of the coating.
[0094] S3: Treating the asphalt with a hydrophobic modifier.
[0095] S31: Preheat the SBS modified asphalt in an oven at 160°C for 0.8 hours to heat it to a flowable state.
[0096] S32: The asphalt is then moved into a constant temperature heating sleeve, and the asphalt is subjected to low-speed shearing at 170°C with a shearing speed of 1250r / min to eliminate bubbles in the asphalt.
[0097] S33: Using the external mixing method, 4% of the hydrophobic material was slowly added to the asphalt within 6 minutes, while stirring with a glass rod.
[0098] S34: The mixture was sheared at a high speed of 3500 r / min for 40 minutes to ensure uniform dispersion of the modifier in the asphalt.
[0099] S35: Keep the modified asphalt in an oven at 170°C for 35 minutes to allow it to react fully.
[0100] S36: Preparation of hydrophobic modified asphalt mixture: According to the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTGE20-2011), the SMA asphalt mixture is designed for mix proportion and the optimal asphalt-stone ratio is determined. According to the determined optimal mix proportion and asphalt-stone ratio, the modified asphalt, modified aggregate and filler are mixed uniformly. The difference between the present invention and the ordinary SMA asphalt mixture is that the asphalt and aggregate are both hydrophobically modified.
[0101] Example 2
[0102] The difference from Example 1 is:
[0103] In S11, tetrabutyl orthosilicate (TBOS):methyltriethoxysilane (MTES)=1:1.
[0104] Example 3
[0105] The difference from Example 1 is:
[0106] In S11, tetrabutyl orthosilicate (TBOS):methyltriethoxysilane (MTES)=3:1.
[0107] Example 4
[0108] The difference from Example 1 is:
[0109] In S12, APMS is 5%.
[0110] Example 5
[0111] The difference from Example 1 is:
[0112] In S12, APMS is 15%.
[0113] Example 6
[0114] S1: Preparation of hydrophobic materials.
[0115] S11: Tetrabutyl orthosilicate (TBOS) and methyltriethoxysilane (MTES) were measured in a molar ratio of 1:1, and 5% of acrylate functionalized silane (APMS) and 30% of anhydrous ethanol were added.
[0116] S12: Place the three-necked flask on a constant temperature magnetic stirrer, stir at a speed of 500 rpm, control the temperature at 50° C., and stir for 40 minutes to allow all materials to be fully dissolved and mixed evenly.
[0117] S13: Deionized water is slowly added using a burette, the volume of the deionized water is 5% of the total solution, the drop rate is controlled at 1 drop / minute, stirring is continued at 50°C for 20 minutes, and the hydrolysis reaction is started. At the same time, ultrasound is used to assist the hydrolysis reaction, the frequency is set to 25kHz, and the ultrasound action time is 20 minutes.
[0118] S14: The temperature was raised to 70°C and the stirring was continued for 40 minutes to allow the silanol (Si-OH) generated by hydrolysis to undergo a condensation reaction to form a cross-linked network. During this process, a high-speed shearing machine was used to shear the solution at a speed of 2000 rpm for 30 minutes to ensure uniform condensation reaction and generate a dense hydrophobic modifier.
[0119] S15: After the condensation reaction is completed, the solution is naturally cooled to room temperature, and the insoluble matter is removed by filtration to obtain a uniform hydrophobic modifier solution.
[0120] S2: Treat aggregate with a hydrophobic modifier.
[0121] S21: After the aggregate is thoroughly washed and dried with clean water, it is placed in a stirrer with small-sized grinding beads and stirred at room temperature for 5 hours to ensure the surface roughness of the aggregate.
[0122] S22: Pour the hydrophobic modifier prepared in S15 into a stirrer, and stir at 20°C for 60 minutes to allow the aggregate surface to fully contact with the hydrophobic modifier.
[0123] S23: Remove the aggregate and rinse it thoroughly with clean water, then put it into an oven at a temperature of 100°C to further promote the silicon-oxygen cross-linking reaction and ensure the stability and durability of the coating.
[0124] S3: Treating the asphalt with a hydrophobic modifier.
[0125] S31: Preheat the SBS modified asphalt in an oven at 155°C for 1 hour to heat it to a flowable state.
[0126] S32: The asphalt is then moved into a constant temperature heating sleeve, and the asphalt is subjected to low-speed shearing at 160°C with a shearing speed of 1000r / min to eliminate bubbles in the asphalt.
[0127] S33: Using the external mixing method, 3% of the hydrophobic material was slowly added to the asphalt within 5 minutes, while stirring with a glass rod.
[0128] S34: The mixture was sheared at a high speed of 3000 r / min for 50 minutes to ensure uniform dispersion of the modifier in the asphalt.
[0129] S35: Keep the modified asphalt in an oven at 165°C for 40 minutes to allow it to react fully.
[0130] S36: Preparation of hydrophobic modified asphalt mixture: According to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTGE20-2011), the mix ratio of SMA asphalt mixture is designed and the optimal asphalt-stone ratio is determined. According to the determined optimal mix ratio and asphalt-stone ratio, the modified asphalt, modified aggregate and filler are mixed evenly.
[0131] Example 7
[0132] S1: Preparation of hydrophobic materials.
[0133] S11: Tetrabutyl orthosilicate (TBOS) and methyltriethoxysilane (MTES) were measured in a molar ratio of 3:1, and 15% of acrylate functionalized silane (APMS) and 50% of anhydrous ethanol were added.
[0134] S12: Place the three-necked flask on a constant temperature magnetic stirrer, stir at a speed of 600 rpm, control the temperature at 60° C., and stir for 20 minutes to ensure that all materials are fully dissolved and mixed evenly.
[0135] S13: Deionized water is slowly added using a burette, the volume of the deionized water is 10% of the total solution, the drop rate is controlled at 2 drops / minute, stirring is continued at 60°C for 10 minutes, and the hydrolysis reaction is started. At the same time, ultrasound is used to assist the hydrolysis reaction, the frequency is set to 35kHz, and the ultrasound action time is 10 minutes.
[0136] S14: The temperature is raised to 80°C and stirring is continued for 30 minutes to allow the silanol (Si-OH) generated by hydrolysis to undergo a condensation reaction to form a cross-linked network. During this process, a high-speed shearing machine is used to shear the solution at a speed of 3000 rpm for 20 minutes to ensure uniform condensation reaction and generate a dense hydrophobic modifier.
[0137] S15: After the condensation reaction is completed, the solution is naturally cooled to room temperature, and the insoluble matter is removed by filtration to obtain a uniform hydrophobic modifier solution.
[0138] S2: Treat aggregate with a hydrophobic modifier.
[0139] S21: After the aggregate is thoroughly washed and dried with clean water, it is placed in a stirrer with small-sized grinding beads and stirred at room temperature for 7 hours to ensure the surface roughness of the aggregate.
[0140] S22: Pour the hydrophobic modifier prepared in S15 into a stirrer, and stir at 30° C. for 30 minutes to allow the aggregate surface to fully contact with the hydrophobic modifier.
[0141] S23: Remove the aggregate and rinse it thoroughly with clean water, then put it into an oven at a temperature of 120°C to further promote the silicon-oxygen cross-linking reaction and ensure the stability and durability of the coating.
[0142] S3: Treating the asphalt with a hydrophobic modifier.
[0143] S31: Preheat the SBS modified asphalt in an oven at 165°C for 0.5 hours to heat it to a flowable state.
[0144] S32: The asphalt is then moved into a constant temperature heating sleeve, and the asphalt is subjected to low-speed shearing at 175°C with a shearing speed of 1500r / min to eliminate bubbles in the asphalt.
[0145] S33: Using the external mixing method, 5% of the hydrophobic material was slowly added to the asphalt within 7 minutes, while stirring with a glass rod.
[0146] S34: The mixture is sheared at a high speed of 4000 r / min for 30 minutes to ensure uniform dispersion of the modifier in the asphalt.
[0147] S35: Keep the modified asphalt in an oven at 175°C for 30 minutes to allow it to react fully.
[0148] S36: Preparation of hydrophobic modified asphalt mixture: According to the "Test Procedure for Asphalt and Asphalt Mixtures for Highway Engineering" (JTGE20-2011), the mix ratio of SMA asphalt mixture is designed and the optimal asphalt-stone ratio is determined. According to the determined optimal mix ratio and asphalt-stone ratio, the modified asphalt, modified aggregate and filler are mixed evenly.
[0149] Comparative Example 1
[0150] The difference from Example 1 is:
[0151] No S1, S2
[0152] In S3, the SBS modified asphalt is hydrophobically modified using a commercially available hydrophobic agent A: dimethoxymethylsilane DMOMS.
[0153] Comparative Example 2
[0154] The difference from Example 1 is:
[0155] No S1, S2
[0156] In S3, the SBS modified asphalt is hydrophobically modified using a commercially available hydrophobic agent B: methyltrimethoxysilane MTMS.
[0157] Comparative Example 3
[0158] The difference from Example 1 is:
[0159] In S11, tetrabutyl orthosilicate (TBOS):methyltriethoxysilane (MTES)=1:3.
[0160] Comparative Example 4
[0161] The difference from Example 1 is:
[0162] In S11, tetrabutyl orthosilicate (TBOS):methyltriethoxysilane (MTES)=4:1.
[0163] Comparative Example 5
[0164] The difference from Example 1 is:
[0165] In S12, APMS is 3%.
[0166] Comparative Example 6
[0167] The difference from Example 1 is:
[0168] In S12, APMS is 20%.
[0169] Comparative Example 7
[0170] The difference from Example 1 is:
[0171] In S14, the temperature is 60°C.
[0172] Comparative Example 8
[0173] The difference from Example 1 is:
[0174] In S14, the temperature is 90°C.
[0175] Comparative Example 9
[0176] The difference from Example 1 is:
[0177] In S14, the rotation speed of the high-speed shearing machine is 1500 rpm.
[0178] Comparative Example 10
[0179] The difference from Example 1 is:
[0180] In S14, the rotation speed of the high-speed shearing machine is 4500 rpm.
[0181] Comparative Example 11
[0182] The difference from Example 1 is:
[0183] In S14, the shearing time is: 15min
[0184] Comparative Example 12
[0185] The difference from Example 1 is:
[0186] In S14, the shearing time is: 45min
[0187] Comparative Example 13
[0188] The difference from Example 1 is:
[0189] No S2.
[0190] Comparative Example 14
[0191] The difference from Example 1 is:
[0192] No S3.
[0193] Table 1 shows the raw material dosage and aggregate asphalt modification of Examples 1 to 5 and Comparative Examples 13 to 14, as shown below:
[0194] Table 1
[0195] the difference TBOS:MTES APMS Quality Score Aggregate modification Asphalt modification Example 1 2:1 10% have have Example 2 1:1 10% have have Example 3 3:1 10% have have Example 4 2:1 5% have have Example 5 2:1 15% have have Comparative Example 13 2:1 10% none have Comparative Example 14 2:1 10% have none
[0196] The hydrophobic SBS modified asphalt mixture prepared in the above example was tested for high and low temperature performance and water stability.
[0197] The high temperature performance of asphalt mixture is determined by rutting test. The test is carried out according to the specification JTG E20-2011. The hydrophobic SBS modified asphalt mixture prepared in the example is used to prepare a standardized asphalt mixture rutting plate specimen with a size of 300mm×300mm×50mm. After sufficient cooling, it is placed at 60°C for 5 hours and moved to a preheated rutting tester. The tester applies a vertical load: the tire pressure is 0.7MPa, the wheel rolling speed is 42 times / min, and the instantaneous deformation of the specimen after each loading is recorded. The test lasts for 60 minutes, during which the deformation of the specimen is continuously recorded.
[0198] The high temperature deformation resistance of asphalt mixture is positively correlated with its dynamic stability.
[0199] The calculation formula of dynamic stability is as follows:
[0200]
[0201] Among them, DS is the dynamic stability of asphalt mixture, d1 is the deformation at time t1, in mm; d2 is the deformation at time t2, in mm; C1 is the testing machine type coefficient, which is taken as 1.0 in this embodiment; C2 is the specimen coefficient, which is taken as 1.0 in this embodiment; N is the test wheel rolling speed, which is set to 42 times / min in this embodiment.
[0202] The low temperature performance of asphalt mixture is determined by beam bending test. The hydrophobic SBS modified asphalt mixture prepared in the embodiment is used to prepare the beam specimen size, the beam specimen size is 250mm×30mm×35mm, the test temperature is -10℃, the insulation time is 4h, and the loading rate of the test machine is 50mm / min. The flexural tensile strength and maximum flexural tensile strain of the specimen during loading are recorded. The calculation formula of the flexural stiffness modulus when the asphalt mixture is damaged is as shown in formula (2)-formula (4):
[0203]
[0204] Maximum bending strain of the specimen at failure (με):
[0205] Bending stiffness modulus of the specimen at failure (MPa):
[0206] Where: b represents the width of the cross section, in mm; h represents the height of the cross section, in mm; L represents the span of the specimen, in mm; P B It represents the maximum load when the specimen is damaged, in N; d represents the mid-span deflection when the specimen is damaged, in mm; ε B is the maximum bending strain of the specimen when it fails, in με, R BIt is the flexural tensile strength of the specimen when it is destroyed.
[0207] The high temperature performance of asphalt mixture is determined by the immersion Marshall test. The test is carried out according to the specification JTG E20-2011. The control group needs to be immersed at 60℃ for 0.5h, and the test group needs to be immersed at 60℃ for 48h before the Marshall stability test is carried out to test the durability and stability of asphalt mixture in high temperature and humid environment. The stability and flow value during the test are recorded.
[0208] Figure 2 The rutting test results of Examples 1 to 7 are shown in the figure. It can be seen from the data in the figure that Example 1 has the highest dynamic stability and shows the best deformation resistance, that is, tetrabutyl orthosilicate (TBOS): methyltriethoxysilane (MTES) = 2:1, APMS mass fraction is 10%, and both aggregate and asphalt are modified, achieving a balanced and optimized modification effect.
[0209] The dynamic stability of Examples 2 and 3 is slightly lower than that of Example 1, but still remains at a high level, which shows that in the change of the ratio of TBOS:MTES (1:1 and 3:1), although the performance has changed, the overall hydrophobic modification effect is still good. This also verifies that although the ratio of TBOS to MTES is important, its effect on dynamic stability is not as significant as changing the mass fraction of APMS.
[0210] The dynamic stability of Examples 4 and 5 is relatively low, which is consistent with the previous analysis, indicating that after the APMS mass fraction is adjusted to 5% or 15%, the performance of the hydrophobic agent decreases, resulting in a weakened deformation resistance of the mixture.
[0211] The dynamic stability of Example 6 and Example 7 is lower than that of Example 1, indicating that the lowest or highest value within the range of all material proportions will affect the modification effect of the hydrophobic agent on the high-temperature stability of the asphalt mixture.
[0212] Figure 3 The rutting test results of Comparative Examples 3 to 14 are shown in the figure. As can be seen from the figure, the dynamic stability values of Comparative Examples 3 and 4 are lower than those of Examples 1, 2, and 3. It can be seen that when the ratio of TBOS:MTES changes beyond the range value (1:1-3:1), it will affect the cross-linking density of the hydrophobic material, the ratio of TBOS to MTES will affect the cross-linking density, and the cross-linking density will affect the flexibility of the material.
[0213] The dynamic stability values of Comparative Examples 5 and 6 are lower than those of Examples 4 and 5, which indicates that when the dosage of the activator acrylate functionalized silane (APMS) exceeds the range value (5% to 15%), it will affect the crosslinking effect of TBOS / MTES. Excessive APMS dosage leads to excessive or low crosslinking density between TBOS and MTES. Changes in crosslinking density directly affect the mechanical properties and high-temperature stability of the material. Too high a crosslinking density may cause the material to become brittle, while insufficient crosslinking density will reduce the strength and toughness of the material. Both of these situations may lead to a decrease in dynamic stability.
[0214] The dynamic stability values of Comparative Examples 7, 8, 9, 10, 11, and 12 are all lower than those of the embodiments. It can be seen that when the hydrolysis temperature, hydrolysis speed, and hydrolysis time are out of range, the hydrolysis and crosslinking efficiency of the hydrophobic agent will be affected, thereby affecting the high temperature flexibility.
[0215] The dynamic stability of Comparative Examples 13 and 14 is significantly lower than that of the embodiment, especially Comparative Example 13 shows the lowest dynamic stability. This verifies the previous speculation that when the modification step of aggregate or asphalt is missing, the bonding force and water damage resistance of the material are significantly reduced, especially when the aggregate is not modified (Comparative Example 13), the dynamic stability is reduced to the minimum, which shows the key role of aggregate modification in improving the overall performance of the material.
[0216] Figure 4 The graph is a graph of the low temperature bending beam test results of Examples 1 to 7. As can be seen from the graph, Example 1 has the highest stiffness modulus, indicating that this example has the best bending resistance and stiffness under low temperature conditions.
[0217] The stiffness modulus of Example 2 and Example 3 is slightly lower than that of Example 1, but still remains at a high level, which shows that although the adjustment of the ratio of TBOS to MTES will affect the final properties of the material, the overall modification effect can still maintain good low-temperature flexural properties.
[0218] The stiffness modulus of Example 4 and Example 5 is lower than that of Example 1, which is consistent with the previous trend of dynamic stability, indicating that after the APMS mass fraction is adjusted to 5% or 15%, the effect of hydrophobic modification is significantly weakened, resulting in a decrease in the rigidity and crack resistance of the mixture at low temperatures.
[0219] The stiffness modulus of Example 6 and Example 7 is lower than that of Example 1-5, indicating that the lowest and highest values of the hydrophobic agent material range will affect the hydrophobic agent effect.
[0220] Figure 5This is a graph of the low-temperature bending beam test results of Comparative Examples 3 to 14. It can be seen from the graph that the stiffness modulus values of Comparative Examples 3 and 4 are lower than those of Examples 1, 2, and 3. It can be seen that when the ratio of TBOS:MTES changes beyond the range value (1:1-3:1), it affects the cross-linking density of the hydrophobic material, thereby affecting the low-temperature flexibility of the asphalt mixture. This is because when the ratio of TBOS:MTES is too large, the cross-linking density increases. Although high cross-linking density may enhance the strength of the material, it will cause the material to become more brittle. High cross-linking density reduces the free movement space of the molecular chain, making the material lack sufficient flexibility at low temperatures and difficult to withstand low-temperature bending forces. This brittleness causes the material to crack easily at low temperatures, thereby reducing the stiffness modulus and showing poor low-temperature flexibility.
[0221] The stiffness modulus values of Comparative Examples 5 and 6 are lower than those of Examples 4 and 5, which indicates that when the dosage of acrylate functionalized silane (APMS) exceeds the recommended range (5% to 15%), the cross-linking effect of the material will be negatively affected, thereby reducing the modification effect of the hydrophobic agent on the asphalt mixture.
[0222] The stiffness modulus values of Comparative Examples 7, 8, 9, 10, 11, and 12 are all lower than those of the embodiments, indicating that the key process parameters (such as hydrolysis temperature, hydrolysis speed, and hydrolysis time) in the hydrolysis process have a significant effect on the hydrolysis crosslinking efficiency of the hydrophobic agent. When these process conditions exceed a reasonable range, the hydrolysis reaction efficiency is reduced, and the crosslinking is insufficient, resulting in the inability to fully exert the performance of the hydrophobic modifier. This ultimately affects the low-temperature crack resistance of the asphalt mixture, which is manifested as a significant decrease in the stiffness modulus.
[0223] The stiffness modulus of Comparative Examples 13 and 14 is significantly reduced, especially Comparative Example 13 shows the lowest stiffness modulus, indicating that the low-temperature performance of the mixture is greatly reduced in the absence of aggregate or asphalt modification steps. In particular, when the aggregate is not modified (Comparative Example 13), the stiffness and crack resistance of the material are significantly insufficient, further emphasizing the key role of aggregate modification in improving low-temperature crack resistance.
[0224] Figure 6 It is a diagram of the results of the submerged Marshall test of Examples 1 to 7. It can be seen from the diagram that Example 1 has the best comprehensive performance in terms of dynamic stability and flow value, indicating that this example has the best anti-deformation ability and structural stability under high temperature conditions.
[0225] The dynamic stability of Example 2 and Example 3 is slightly lower than that of Example 1, but still remains at a relatively high level. The flow value is slightly higher than that of Example 1, and the overall high-temperature deformation resistance is still relatively strong.
[0226] The dynamic stability of Examples 4 and 5 is lower, and the flow value is slightly higher than that of Example 1, which is consistent with the previous analysis and shows that after the APMS mass fraction is adjusted to 5% or 15%, the effect of hydrophobic modification is weakened, resulting in the mixture's deformation resistance and durability at high temperature being inferior to that of Example 1.
[0227] The flow values of Examples 6 and 7 are higher than those of Examples 1-5, and the stability values are lower than those of Examples 1-5, indicating that the amount of hydrophobic material added at the upper or lower limit of the range value will result in the mixture's water damage resistance and structural performance being inferior to those of Example 1.
[0228] Figure 7 The results of the submerged Marshall test of Comparative Examples 3 to 14 are shown in the figure. It can be seen from the figure that the flow value and stability value of Comparative Examples 3 and 4 are inferior to those of Examples 1, 2, and 3. It can be seen that when the ratio of TBOS:MTES changes beyond the range value (1:1-3:1), the water stability of the asphalt mixture decreases significantly. The ratio of TBOS to MTES is crucial to the hydrophobic properties of the material. Imbalance in the ratio will affect the water stability of the mixture, resulting in an increase in the flow value and a decrease in stability in a submerged environment.
[0229] The flow value and stability value of Comparative Examples 5 and 6 are inferior to those of Examples 4 and 5, which indicates that when the dosage of the activator acrylate functionalized silane (APMS) exceeds the recommended range (5% to 15%), the excessive or insufficient APMS dosage will affect the dispersion and activation of the hydrophobic agent, thereby affecting the modification effect on the water stability of the asphalt mixture.
[0230] The flow values and stability values of Comparative Examples 7, 8, 9, 10, 11, and 12 are inferior to those of the embodiments, indicating that the key process parameters (such as hydrolysis temperature, hydrolysis speed, and hydrolysis time) in the hydrolysis process have a significant effect on the hydrolysis crosslinking efficiency of the hydrophobic agent. If the hydrolysis process parameters are improperly controlled, the hydrophobic agent cannot form a stable crosslinked network, resulting in a decrease in the water damage resistance of the mixture, which is manifested as an increase in the flow value and a decrease in stability after immersion.
[0231] The dynamic stability of Comparative Examples 13 and 14 was significantly reduced, and the flow value was significantly increased. In particular, Comparative Example 13 showed the lowest dynamic stability and poor flow value, which indicated that the high temperature performance of the mixture was greatly reduced in the absence of aggregate or asphalt modification steps. In particular, when the aggregate was not modified (Comparative Example 13), the structural stability and deformation resistance of the material were significantly weakened, further emphasizing the key role of asphalt modification in improving high temperature performance.
[0232] Contact angle tests were performed on SBS asphalt (as a blank control group), SBS / A obtained in Comparative Example 1, SBS / B obtained in Comparative Example 2, and SBS / self-made hydrophobic modified asphalt in Example 1. Figure 8The test shows that SBS / self-made hydrophobic modified asphalt has significant advantages in improving the performance of asphalt mixture. Compared with the control group SBS, the adhesion work of the self-made hydrophobic modifier increased from 55.34 to 64.54, an increase of about 16.5%, significantly improving the bonding strength between asphalt and aggregate. Compared with the commercially available hydrophobic agents A (44.36) and B (56.44), the adhesion work of the self-made hydrophobic modifier was greatly improved, showing a better effect. In terms of compatibility, the self-made hydrophobic modifier reached 0.622, significantly higher than A (0.477) and B (0.578), further proving its excellent performance in improving the compatibility between asphalt and aggregate. These data show that the self-made hydrophobic modifier is not only superior to the blank control group SBS, but also significantly superior to the commercially available hydrophobic agents A and B in performance, making the asphalt mixture perform better in water stability and bonding strength.
[0233] See also Fig. 9 It can be clearly seen that the asphalt mixture prepared by the present invention is different from the modified asphalt prepared by the existing hydrophobic agent, namely SBS / A obtained in Comparative Example 1 and SBS / B obtained in Comparative Example 2. The asphalt mixture prepared by the present invention significantly improves the structural stability and deformation resistance, and improves the high temperature performance.
[0234] See also Fig.10 , Marshall specimens were prepared using SBS modified asphalt mixture (as blank control group), Example 1, Comparative Example 1, and Comparative Example 2, and freeze-thaw fatigue cracking tests were carried out. The test data showed that the residual stability of the asphalt mixture of Example 1 in all test environments was significantly higher than that of the asphalt mixture of the blank control group. Specifically, in the acid rain environment (A), the residual stability of the asphalt mixture of Example 1 was 0.91, significantly higher than 0.81 of SBS modified asphalt; in the normal rain environment (N), the residual stability of the asphalt mixture of Example 1 was 0.88, while that of SBS modified asphalt was 0.84; in the seawater environment (S), the residual stability of the asphalt mixture of Example 1 reached 0.87, higher than 0.86 of SBS modified asphalt. These data show that hydrophobic modification significantly enhances the water damage resistance of the asphalt mixture, enabling it to maintain high stability and durability in different harsh water environments.
[0235] The residual stability of the asphalt mixtures of Comparative Examples 1 and 2 in different rainwater environments is lower than that of Example 1, indicating that compared with the prior art, the hydrophobic modifier in Example 1 has better adaptability in different water environments.
[0236] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0237] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrophobic modified asphalt mixture, characterized in that: The following steps are involved: S1: preparing a hydrophobic modifier; S2: Aggregate treatment with hydrophobic modifier; S3: Treating asphalt with a hydrophobic modifier and preparing a hydrophobic modified asphalt mixture.
2. The method for preparing a hydrophobic modified asphalt mixture according to claim 1, characterized in that: The S1 includes: S11: mix tetrabutyl orthosilicate and methyltriethoxysilane, add acrylate functionalized silane to the mixed solution, and then add anhydrous ethanol; S12: heating and stirring the solution obtained in S11; S13: adding deionized water to the solution obtained in S12 to perform a hydrolysis reaction, heating and stirring the solution; and simultaneously using ultrasound to assist the reaction; S14: increasing the heating temperature to perform a condensation reaction, and performing a shearing treatment on the solution while stirring the solution; S15: After the condensation reaction is completed, the solution is cooled and filtered to obtain a hydrophobic modifier.
3. The method for preparing the hydrophobic modified asphalt mixture according to claim 2, characterized in that: In the S11, The molar ratio of tetrabutyl orthosilicate to methyltriethoxysilane is (1:1) to (3:1); The volume ratio of acrylate functionalized silane to tetrabutyl orthosilicate is 5% to 15%; The volume ratio of anhydrous ethanol to the total volume of tetrabutyl orthosilicate and methyltriethoxysilane is 30%-50%.
4. The method for preparing the hydrophobic modified asphalt mixture according to claim 2, characterized in that: In S12, the stirring speed is 500-600 rpm; the temperature is 50-60° C., and the stirring time is 20-40 minutes; In S13, the volume of deionized water is 5-10% of the total volume of the solution obtained in S12, the temperature is 50-60° C., the stirring time is 10-20 minutes, the ultrasonic frequency is 25-35 kHz, and the ultrasonic action time is 10-20 minutes.
5. The method for preparing the hydrophobic modified asphalt mixture according to claim 2, characterized in that: In the S14, the temperature is 70-80°C, the stirring time is 30-40 minutes, the solution is sheared at a rotation speed of 2000-3000 rpm, and the shearing time is 20-30 minutes.
6. The method for preparing the hydrophobic modified asphalt mixture according to claim 1 or 2, characterized in that: The S2 includes: S21: washing and drying the aggregate, and stirring in a stirrer; S22: adding the prepared hydrophobic modifier into the stirrer of S21 and stirring; S23: taking out the aggregate, cleaning it and heating it to obtain modified aggregate.
7. The method for preparing the hydrophobic modified asphalt mixture according to claim 6, characterized in that: In S21, the aggregate is stirred in a stirrer for 5 to 7 hours; In S22, the temperature is 20-30°C and the stirring time is 30-60 min; In S23, after cleaning, the aggregate is placed in a heating container for heating at a temperature of 100 to 120°C.
8. The method for preparing the hydrophobic modified asphalt mixture according to claim 1, characterized in that: The S3 includes: S31: heating the SBS modified asphalt to a flowable state; S32: shearing the asphalt; S33: adding the prepared hydrophobic modifier to asphalt; S34: shearing the mixture obtained in S33 to obtain modified asphalt; S35: heating the modified asphalt; S36: Mixing the heated modified asphalt, modified aggregate, and filler to obtain a hydrophobic modified asphalt mixture.
9. The method for preparing the hydrophobic modified asphalt mixture according to claim 8, characterized in that: In the S31, the heating temperature is 155-165° C. and the heating time is 0.5-1 hour; In S32, the asphalt is sheared at 160-175°C and the shearing speed is 1000-1500 r / min; In S33, the mass of the hydrophobic modifier is 3% to 5% of the mass of the asphalt, and the hydrophobic modifier is added to the asphalt within 5 to 7 minutes; In S34, the shearing speed is 3000-4000 r / min, and the shearing time is 30-50 minutes; In S35, the heating temperature is 165 to 175°C and the heating time is 30 to 40 minutes.
10. The hydrophobic modified asphalt mixture prepared by the method for preparing the hydrophobic modified asphalt mixture according to any one of claims 1 to 9.